Beyond Safety: Do Sustainability Supply Chain Practices Drive Community Development in Mining? Insights From Indonesia - Mukhlas Sumartanto; Eka Cempaka Putri (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: The mining industry plays a significant role in the national economy but poses substantial environmental and social challenges. Sustainability has become a global priority, emphasized through initiatives such as the Sustainable Development Goals (SDGs). Among these, community welfare is a key focus area that mining companies are expected to support. Regulation No. 3 of 2020 on mineral and coal mining mandates that companies demonstrate social responsibility and environmental stewardship. However, implementation gaps persist, particularly in the post-mining phase, where neglected infrastructure and unresolved community concerns regarding environmental degradation threaten long-term development objectives.Purpose: This study investigates the influence of Green Supply Chain Management (GrSCM) practices, namely Internal Environmental Management, Green Purchasing, and Investment Recovery, on Community Development, with Occupational Health and Safety (OHS) as a mediating variable. Design/Methodology/Approach: A quantitative approach was employed, utilizing data from 144 respondents across Indonesian mining companies. The structural relationships were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Finding/Result: The results indicate that all three GrSCM practices have significant and positive direct effects on Community Development, highlighting their role in supporting the SDGs. Among them, only Internal Environmental Management has a significant effect on OHS. Additionally, while OHS has a direct positive effect on Community Development, it does not mediate the relationship between GrSCM practices and Community Development.Conclusion: These findings suggest that sustainable operational practices in mining contribute directly to community outcomes, rather than through improvements in safety performance alone.Originality/value/research gap: This study contributes to sustainability research by clarifying the distinct roles of environmental management and occupational safety in promoting community development within the mining sector. Keywords: green supply chain management, community development, occupational health and safety, sustainable development goals, mining industry in indonesia